The multicultural challenge - Brochmann, Grete (Comparative social research ;, 2003)
Cultural pluralisation - reinforced by immigration - has had major consequences for the political agenda in recent years in liberal democratic states. New types of tension have arisen - new forms of social and cultural differentiation, and new patterns of inequality. The diversity also reshapes the frame of reference for traditional policy instruments employed by modern welfare states: new issues arise that are linked to rights, legitimacy and policy measures of a general and targeted nature. This volume in the "Comparative Social Research" series addresses a number of issues related to this new diversity. Common themes are multiculturalism, power and integration, and these themes are analysed through a comparative lens.